Trustee board diversity, governance mechanisms, capital structure and performance in UK charities - Mohamed Elmagrhi (Corporate Governance: The International Journal of Business in Society, 2018)
Purpose: We investigate the association among trustee board diversity (TBD), corporate governance (CG),capital structure (CS) and financial performance (FP) using a sample of UK charities. Specifically, weinvestigate the effect of TBD on CS, and ascertain whether CG quality moderates the TBD-CS nexus.Additionally, we examine the impact of CS on FP, and ascertain whether the CS-FP nexus is also moderatedby TBD and CG quality.Design/methodology/approach: We employ a number of multivariate regression techniques, includingordinary least squares, fixed-effects, lagged-effects and two-stage least squares to rigorously analyse the dataand test the hypotheses.Findings: First, we find that trustee board gender diversity has a negative effect on CS, but this relationshipholds only up to the point of having three women trustees. We find similar, but relatively weak results for thepresence of Black, Asian and Minority Ethnic trustees. Second, we find that the TBD-CS nexus depends onthe quality of CG with the relationship being stronger in charities with higher frequency of meetings,independent CG committee, and larger trustee and audit firm size. Third, we find that CS structure has apositive effect on FP, but this is moderated by TBD and CG quality. Our evidence is robust to differenteconometric models that adjust for alternative measures and endogeneities. We interpret our findings withinthe explanations of a theoretical perspective that captures insights from different CG and CS theories.Originality/value: Existing studies on TBD, CG, CS and FP in charities are rare. Our study distinctivelyattempts to address this empirical lacuna within the extant literature by providing four new insights withspecific focus on UK charities. First, we provide new evidence on the relationship between TBD and CS.Second, we offer new evidence on the moderating effect of CG on the TBD-CS nexus. Third, we provide newevidence on the effect of CS on FP. Finally, we offer new evidence on the moderating effect of TBD and CGon the CS-FP nexus.